Perilaku Dakwah Komunitas Desainer Muslim di Jombang - Harris Azis; Ali Imron (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2021)
Muslim Designer Community Chapter Jombang, a community that is active in social activities such as Islamic studies, training, talk shows, exhibitions of visual da'wah works, and so on. The phenomenon of preaching through visuals indicates that now graphic da'wah has received wide attention and is in demand by various circles of society. Then how is the behavior of the Muslim Designer Community Chapter Jombang preaching? What is the influence of preaching activities through graphics / visual communication? This study uses a qualitative research type with a case study approach with phenomenological data analysis techniques. The results showed that the preaching behavior of Muslim Designer Community Chapter Jombang in carrying out graphic da'wah can be seen in two phases, namely because-motive and motive-for (in-orderto-motive). The reasons that were found were: learning motive (learn). and the motive for sharing (share). Meanwhile, the influence of the delivery of da'wah through graphic media by the Muslim Designer Community Chapter Jombang covers three aspects, namely cognitive, affective and behavioral aspects.